A new classification system and an algorithm for the reconstruction of nasal defects - BAYRAMİÇLİ, MEHMET NURİ ÜMİT (ELSEVIER SCI LTD, 2006)
A new, comprehensive system for scoring and classification of nasal defects is proposed in this article. The soft tissue coverage of the nose is in continuity with the cheeks, glabella and upper tip and the osteocartitaginous infrastructure is in continuity with the two nasofrontat buttresses, the frontal bar and the palate. Soft tissues and the skeletal framework are divided into sub-units and these anatomic features are schematized on a logo. The sub-units are graded on the logo, depending on their gravity in reconstructive strategies. Any given nasal defect is described by shading the involved sub-units on the Logo and the sum of the points appended each sub-unit gives the total score of defect. The severity of the tissue toss is assessed according to a Classification System which is derived from this scoring system. Nasal defects are classified into one of four main Types corresponding to their scores. One hundred twenty seven patients who were operated on for various nasal. pathologies have been reviewed and nasal defects are scored and classified according to the proposed system. Application of this system to the spectrum of cases encountered in a 6 years period shows that it is based on anatomic grounds, easy to document and efficient transmission of objective information becomes possible. It also offers a useful algorithm to approach the reconstruction of nasal defects. (c) 2006 The British Association of Plastic Surgeons. Published by Elsevier Ltd. All rights reserved.
Keywords: nasal defects; classification; reconstruction; MIDFACIAL DEFECTS; NECK RECONSTRUCTION; SUBUNIT PRINCIPLE; FLAPS; HEAD; TIP